Degradation study of Bromelain-extracted virgin coconut oil based on peroxide and fatty acid formation under the elevated temperatures - Harimurti, Sabtanti; Prayogo, Galih Kukuh; Widada, Hari; Orbayinah, Salmah; Sukamdi, Dyani Primasari; Erviana, Rima; Amid, Azura; Tho, Do Chau Minh Vinh (EDP Sciences, 2024)
This research seeks to ascertain the kinetic parameters of VCO degradation based on the formation of peroxide and free fatty acids and to evaluate the shelf life of bromelain-extracted VCO at various temperatures. The kinetic parameters and shelf life of VCO were determined by measuring the value of peroxides and free fatty acids (FFA) concentration at temperatures of 50 ºC to 200 ºC. The heating was performed in a 1 L conical flask immersed in the paraffin bath. Samples were collected for each temperature at 0 to 60 minutes. The rate constant of peroxide and FFA formation was determined by regression analysis using Microsoft Excel, based on the plot of sampling time and value of peroxide and FFA concentration. The rate constant of peroxide formation escalated from 0.0114 to 0.1419 mEq Kg-1 min-1 when the VCO was heated at 50 ºC to 200 ºC. Meanwhile, the rate constant of FFA formation rose from 0.0188 to 0.0393 % min-1 when subjected to heating at 50 ºC to 200 ºC. Based on the shelf-life prediction established by Indonesian National Standards or the Asian and Pacific Coconut Community, the shelf-life of bromelain extracted VCO varies from 10 to 3 hours at temperatures ranging from 2 ºC to 50 ºC. It was determined that elevating the temperature reduced the shelf-life of bromelain-extracted VCO. These findings suggest that temperature is crucial for the stability of bromelain-extracted VCO.